Technical constraints to ruminant livestock production in sub-Saharan Africa - Kaufmann, Ralph R. von; Fitzhugh, H.A. (British Society of Animal Production, 1993)
Constraints do not only occur in production systems. They also limit the support available from research and extension and they have serious consequences for human welfare in Africa and for the whole community of nations. The agricultural research agendas in sub-Saharan Africa are indicating more concern for appropriate technology and interest in collaboration but support for research is declining when it is most urgently needed. Food production in sub-Saharan Africa is not keeping pace with demand and this is a cause of instability that will constraint all other attempts at Development. The effect of the constraints is most evident on the deteriorating environment which is evident in each agro-ecological zone despite the different potentials and pressures. Animal productivity is low but has the potential for substantial improvement. Misconceptions and a lack of faith in the potential for improvement are themselves constraints in the sense that they discourage donor support for research to alleviate the real problems. Opportunities for improvement have been identified in each agro-ecological zone. There are three major categories of research institutions: national agricultural research centres and developed country research centres. Each has its own comparative advantages and vital role to play in collaboration with the others. With the limitation in research resources there is an urgent need to develop appropriate research methods and techniques that can be applied sufficiently to have impact across the whole of sub-Saharan Africa. These are particularly required in regard to food production. Research opportunities are identified in plant genotypes, animal health, animal genotypes and extension and input supply.